Polyosma penibukanensis - Hoo, P.K.; Colin Ruzelion Maycock; Damit, A.; Khoo, E.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Tsen, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Polyosma penibukanensis is restricted to Mount Kinabalu. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 20 km2 and are not in decline. It is protected within Kinabalu Park, a Totally Protected Area (TPA). The serious plausible threats are landslide and climate change which could potentially drive the species towards Critically Endangered or Extinct in the near future. Hence, it is assessed as Vulnerable. Polyosma penibukanensis is endemic to Sabah, Malaysia. It is restricted to Mount Kinabalu.